2020
DOI: 10.1016/j.drugalcdep.2020.108182
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of cannabis use and risk for opioid misuse in a young adult urban cohort

Abstract: Background-Although much of the attention surrounding the opioid epidemic has focused on rural and suburban Whites and prescription opioids, heroin overdoses among urban Blacks are on the rise. While some argue that legalization of cannabis will combat the epidemic, there are concerns it ignores the shift in the epidemic and could increase vulnerability to opioid misuse. The goal of this study is to examine the association between cannabis use from adolescence to young adulthood with opioid misuse in a primari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 70 publications
1
7
0
Order By: Relevance
“…Early cannabis users had between two and 14 times the odds of using other drugs compared with non-users ( 34 , 41 , 42 , 68 , 88 , 135 ). After covariates adjustment, these odds were increased to between two and 17 times ( 34 , 62 , 88 , 135 ), or became non-significant ( 149 ). These results are in line with increased prevalence of a range of illicit drug uses among early cannabis users compared with non-users ( 47 , 85 ), especially in frequent cannabis users ( 143 ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Early cannabis users had between two and 14 times the odds of using other drugs compared with non-users ( 34 , 41 , 42 , 68 , 88 , 135 ). After covariates adjustment, these odds were increased to between two and 17 times ( 34 , 62 , 88 , 135 ), or became non-significant ( 149 ). These results are in line with increased prevalence of a range of illicit drug uses among early cannabis users compared with non-users ( 47 , 85 ), especially in frequent cannabis users ( 143 ).…”
Section: Resultsmentioning
confidence: 98%
“…Stanley et al ( 137 ) reported that while late cannabis users had 16 times the odds of misusing prescription drugs compared with non-users, early cannabis users had 47 times these odds. Early cannabis initiators had twice the odds of misusing prescription opioids compared with non-users ( 135 ), and nearly twice the risk of prescription opioid misuse compared with late users ( 129 ). This contrasts with Moss et al ( 85 ) findings of similar prevalence of pain reliever misuse between early cannabis users and non-users.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, several studies have found that medical cannabis patients report pain management as one of the most common reasons for cannabis use [10][11][12] and that cannabis use was associated with lower opioid use among people who use illicit drugs [13,14]. However, there are also ongoing concerns about cannabis use increasing the risk for non-medical opioid use and opioid and cannabis use disorders, especially among adolescents and young adults [15][16][17][18], and that cannabis use may lead to return to opioid use by people with a history of OUD [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Cannabis co-use triples the risk of dependence on heroin in those diagnosed with a substance use disorder (Crummy et al, 2020) and cannabis users over 50 years of age exhibit a 6.3 increased odds ratio of heroin use (Ramadan et al, 2020). Adolescents in one urban setting who use cannabis regularly are at twice the risk for opioid misuse compared with occasional users of cannabis (Reboussin et al, 2020) and age 14 onset of frequent cannabis use increases the risk of opioid use at age 19 (Thrul et al, 2020). Almost two thirds of individuals in one sample first used heroin while co-using cannabis (Olthuis et al, 2013) and 50-60% of individuals in heroin-maintenance and methadone-maintenance treatment for opioid use disorder were co-using cannabis (Musshoff et al, 2010).…”
Section: Introductionmentioning
confidence: 99%